An Evaluation of APRM Communication Strategy - Atam, Millan (My University, 2011)
In 2003, a decision was taken by African Heads of State and Government to establish the Peer Review Mechanism (APRM), a voluntary initiative, which had as goal to enable member states to assess and assist each other in conforming to economic, political and corporate governance standards and ethics amongst others. By the end of the first year, twenty-three African countries had voluntarily acceded to the APRM and by the time of this research it had 29 members, being over fifty percent of the overall African Union membership. This initiative brought with it high hopes and expectations for the peoples of the African continent. Six years later, the African Peer Review Mechanism is still struggling to assert itself. While it has been able to achieve some results, why is it that a lot of these is still largely unknown across the continent? There was reason therefore to believe that effective communication is the probable culprit. The APRM Secretariat and Panel of Eminent Persons may not have invested enough in finding channels of accountability and information to the average African. This has resulted in the current apathy towards the APRM agenda across the continent and even amongst member countries. This research is aimed at evaluating the communication strategy of the APRM, and to assess if the lack of buy-in and active participation from stakeholders could perhaps hinge solely on the lack of appropriate communication or if there are other contributing factors. Through in-depth interviews and a number of field visits, this research has been able to use qualitative research to establish that indeed there is no structured communication strategy within the APRM Secretariat, which is supposed to be the engine-room of APRM efforts. But then, it also establishes that communication is only one of the many shortcomings of the APRM. Others include; poor management, lack of transparency and accountability which seem to be the root causes for the Secretariat being unable to carry out its tasks effectively. This study therefore recommended that in order to resolve the problem of communication, there is need to re-evaluate the role of the Panel, the Secretariat, the Country Offices and put in place checks and balances that would address the root problems
MM - P&DM
Keywords: African Peer Review Mechanism; Corporate governance